2022
DOI: 10.3389/fendo.2021.800398
|View full text |Cite
|
Sign up to set email alerts
|

High-Contrast Lumbar Spinal Bone Imaging Using a 3D Slab-Selective UTE Sequence

Abstract: Ultra-short echo time (UTE) MRI with post-processing is a promising technique in bone imaging that produces a similar contrast to computed tomography (CT). Here, we propose a 3D slab-selective ultrashort echo time (UTE) sequence together with image post-processing to image bone structures in the lumbar spine. We also explore the intermodality agreement between the UTE and CT images. The lumbar spines of two healthy volunteers were imaged with 3D UTE using five different resolutions to determine the best imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Note the retropulsion of a bone fragment in T12 narrowing the spinal canal and its proximity to the spinal cord, which can be seen on the UTE sequence (yellow arrowheads in B and F). This figure was previously presented by Afsahi et al 36 Licensed under CC BY 4.0.…”
Section: Ultrashort Echo Time Mrimentioning
confidence: 73%
See 1 more Smart Citation
“…Note the retropulsion of a bone fragment in T12 narrowing the spinal canal and its proximity to the spinal cord, which can be seen on the UTE sequence (yellow arrowheads in B and F). This figure was previously presented by Afsahi et al 36 Licensed under CC BY 4.0.…”
Section: Ultrashort Echo Time Mrimentioning
confidence: 73%
“…Afsahi et al 36 recently showed the feasibility of a 3D UTE Cones MRI with a slab-selective radiofrequency pulse to image the spine in healthy volunteers and patients with back pain, showing excellent intermodality agreement with CT (Fig. 7).…”
Section: Ultrashort Echo Time Mrimentioning
confidence: 94%
“…The remaining asymptomatic volunteers and symptomatic patients were scanned with the resultant optimized protocol: (i) DIR-UTE: TR/TI 1 /TI 2 = 1500/610/150 ms, TE = 0.032 ms, FA = 10 ° , N sp = 27, FOV = 28 × 28 × 4.32 cm 3 , matrix = 320 × 320 × 12, voxel size = 0.875 × 0.875 × 3.6 mm 3 , bandwidth = 125 kHz, and scan time = 10 min; (ii) IR-FS-UTE [ 19 ]: TR/TI = 1200/600 ms, TE = 0.032 ms, FA = 10 ° , N sp = 21, FOV = 28 × 28 × 4.32 cm 3 , matrix = 320 × 320 × 12, voxel size = 0.875 × 0.875 × 3.6 mm 3 , bandwidth = 125 kHz, and scan time = 10 min; (iii) T 1w -FS-UTE: TR = 120 ms, TE = 0.032 ms, FA = 15 ° , FOV = 28 × 28 × 4.32 cm 3 , matrix = 320 × 320 × 12, voxel size = 0.875 × 0.875 × 3.6 mm 3 , bandwidth = 125 kHz, and scan time = 2 min 20 s; (iv) FS-UTE: TR = 120 ms, TE = 0.032 ms, FA = 6 ° , FOV = 28 × 28 × 4.32 cm 3 , matrix = 320 × 320 × 12, voxel size = 0.875 × 0.875 × 3.6 mm 3 , bandwidth = 125 kHz, and scan time = 2 min 20 s. Clinical T 1w - and T 2w -FSE sequences were scanned for comparison. In addition, for the patient scan, a proton density weighted-UTE (PDw-UTE) sequence with an isotropic resolution (1.2 mm 3 ) was also employed for high contrast cortical bone imaging [ 29 ]. The sequence parameters used in the other UTE sequences were optimized in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…That is presumably because UTE/ZTE sequences allow direct visualization of bones, especially the cortical bones, resulting in preferable diagnostic feasibility. Meanwhile, the superiority of the T1-weighted 3D-GRE sequence for the diagnosis of vertebral fracture and degenerative changes has also been reported [ 25 ]. In the present article, our experience of applying the 3D-GRE sequence (volume incorporated breath-hold examination, VIBE) for the diagnosis of vertebral lesions is presented, unless otherwise specified (Table 2 ).…”
Section: Basic Issues Of Mr Bone Imagingmentioning
confidence: 99%